MGF E peptide improves anterior cruciate ligament repair by inhibiting hypoxia‐induced cell apoptosis and accelerating angiogenesis. Issue 6 (14th October 2018) - Sha, Yongqiang; Yang, Li; Lv, Yonggang
Abstract: Severe hypoxic microenvironment endangers cell survival of anterior cruciate ligament (ACL) fibroblasts and is harmful to ACL repair and regeneration. In the current study, we explored the effects of mechanogrowth factor (MGF) E peptide on the hypoxia‐induced apoptosis of ACL fibroblasts and relevant mechanisms. It demonstrated that severe hypoxia promoted hypoxia‐inducible factor‐1α (HIF‐1α) expression and caused cell apoptosis of ACL fibroblasts through increasing caspase 3/7/9 messenger RNA (mRNA), cleaved caspase 3 and proapoptotic proteins expression levels but decreasing antiapoptotic proteins expression levels. Fortunately, MGF E peptide effectively protected ACL fibroblasts against hypoxia‐induced apoptosis through regulating caspase 3/7/9 mRNA, cleaved caspase 3 and apoptosis‐relevant proteins expression levels. Simultaneously, mitochondrial, @@@MEK‐ERK1/2 (extracellular‐signal‐regulated kinase 1/2), and phosphoinositide‐3‐kinase‐protein kinase B (PI3K‐Akt) pathways were involved in MGF E peptide regulating hypoxia‐induced apoptosis of ACL fibroblasts. In rabbit ACL rupture model, MGF E peptide also decreased HIF‐1α expression levels, cell apoptosis, and facilitated cell proliferation. In addition, MGF could accelerate angiogenesis after ACL injury probably owing to its recruitment of proangiogenesis cells by stromal cell‐derived factor 1α/CXCR4 axis and stimulation of vascular endothelial growth factor α expression level. In conclusion, our findings suggested that MGF E peptide could be utilized for ACL repair and regeneration and supplied experimental support for its application in clinical ACL treatment as a potential strategy. Abstract : Severe hypoxia induces anterior cruciate ligament (ACL) fibroblasts apoptosis by upregulating caspases and Bax expression levels. Mechanogrowth factor (MGF) can weaken the effects of severe hypoxia on the expression levels of caspases, B‐cell lymphoma‐2‐associated X protein, and B‐cell lymphoma‐2. MGF can reduce ACL fibroblasts apoptosis through @@@MEK‐ERK1/2 (extracellular‐signal‐regulated kinase 1/2), and phosphoinositide‐3‐kinase‐protein kinase B (PI3K‐Akt) pathways.